2017
DOI: 10.1111/eth.12631
|View full text |Cite
|
Sign up to set email alerts
|

Eavesdropping in solitary large carnivores: Black bears advance and vocalize toward cougar playbacks

Abstract: Large carnivore behavioral responses to the cues of their competitors are rarely observed, but may mediate competition between these top predators. Playback experiments, currently limited to interactions involving group‐living large carnivores, demonstrate that attending to cues indicative of the immediate presence of heterospecific competitors plays a substantial role in influencing competition among these species. Group‐living species vocalize regularly to signal to one another, and competitors can readily “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…26 , and following the experimental protocol described therein, we conducted a playback experiment with pumas at their active kill sites. While wildlife species respond to a variety of cue types, presentation of vocalizations provides the most reliable method of simulating the immediate presence of a predator or competitor 39 , and indeed dozens of studies have shown that wildlife exhibit strong behavioral responses to just the sounds of their enemies 40,41 . We tracked adult pumas fitted with GPS collars (GPS Plus and Vertex, Vectronics Aerospace, Berlin, Germany) sampling at 4-hour intervals, and identified potential fresh kill sites as clusters of two or more GPS locations occurring between sunset and sunrise and within 100 m of each other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 , and following the experimental protocol described therein, we conducted a playback experiment with pumas at their active kill sites. While wildlife species respond to a variety of cue types, presentation of vocalizations provides the most reliable method of simulating the immediate presence of a predator or competitor 39 , and indeed dozens of studies have shown that wildlife exhibit strong behavioral responses to just the sounds of their enemies 40,41 . We tracked adult pumas fitted with GPS collars (GPS Plus and Vertex, Vectronics Aerospace, Berlin, Germany) sampling at 4-hour intervals, and identified potential fresh kill sites as clusters of two or more GPS locations occurring between sunset and sunrise and within 100 m of each other.…”
Section: Methodsmentioning
confidence: 99%
“…Under the assumption that all sizes of dog are equally likely to be associated with humans, but only large dogs potentially pose a direct threat to pumas, detecting behavioral responses only to the playbacks of large dogs would indicate that the threat of dogs as competitors affects puma behavior, while detecting equally strong responses to both small and large dog playbacks would suggest that dogs are perceived as risky because of their association with humans. Following well established protocols 26,40,42 , we used multiple exemplars of each playback type (seven frog, six small dog, and five large dog), which were standardized to be broadcast at a consistent volume of 80 dB at 1 m (measured using Radioshack 33–2055 Digital Sound Level Meter set to fast response and C weighting). All dog playbacks consisted of a single individual barking.…”
Section: Methodsmentioning
confidence: 99%
“…In support of this hypothesis, individuals with autism-a developmental disorder with social interaction impairments-have also failed to demonstrate reputation formation (Izuma et al, 2011). Furthermore, Suraci et al (2017) provided evidence for possible eavesdropping in black bears, which are relatively solitary, and Herrmann et al (2013) found that both orangutans and chimpanzees approached nice versus mean experimenters after indirect observations. These findings are consistent with our view that the distinction between social and asocial species is less useful for predicting skill sets, social and physical, than presently assumed.…”
Section: Generalizing From Others' Knowledgementioning
confidence: 98%
“…While bears possess acute senses, it is unlikely there was sufficient time for olfactory cues to alert multiple bears within such a short time, and because the event occurred at night, visual cues would have been limited. Recent analysis has shown vocalizations by young cougars are highly audible (Allen et al, 2016) and attract rather than repel bears (Suraci et al, 2017), which likely prompted the aggregation of bears and increased threat of predation (Hughes et al, 2012). The first bear to arrive at the nursery, U9, may have been alerted because of vocalizations made by either nurslings or C256.…”
Section: Animal Id Species Sex Mass (Kg) Collar Model; Make Programme...mentioning
confidence: 99%